A Comparison of Concrete-Representational-Abstract and Concrete-Representational-Abstract-Integrated Fraction Interventions for Students with Disabilities. Issue 2 (14th March 2020) - Morano, Stephanie; Flores, Margaret M.; Hinton, Vanessa; Meyer, Jillian
ABSTRACT: This study compares the effects of a concrete-representational-abstract (CRA) intervention against a modified CRA-Integrated (CRA-I) intervention using a pretest-posttest design with random assignment of matched pairs to intervention conditions. The researchers designed both interventions to improve participants' understanding of and ability to apply unit fraction and fraction equivalence concepts. Participants were 28 fifth and sixth graders with disabilities. Results indicate that CRA and CRA-I both led to similarly large pre-to-post performance gains ( ES  = .95 on posttest and .80 on a fraction number line estimation test).